Effects of rate of force development on EMG amplitude and frequency - Ricard, M. D.; Ugrinowitsch, C.; Parcell, A. C.; Hilton, S.; Rubley, M. D.; Sawyer, R.; Poole, C. R. (International Journal of Sports Medicine, 2005)
The purpose of this study was to compare the amplitude and frequency of the gastrocnemius EMG during ramp and ballistic contractions in highly trained sprint athletes. Sixteen female sprinters performed ramp and ballistic isometric contractions on a Biodex dynamometer. RMS and median frequency of the gastrocnemius EMG signals were obtained at the following torque levels: 25 ± 5 %, 50 ± 5 %, 75 ± 5 %, 100 % MVC. The average rate of force development (RFD), was 610.2 ± 123.1 N · m/s and 212.3 ± 155.6 N · m/s for the ballistic and ramp contractions, respectively. In the ramp contractions the EMG amplitude increased as a function of torque. In the ballistic contractions the EMG amplitude decreased from 25 % to 100 % MVC. The highest RFD of 889.45 N · m/s was generated in ballistic contractions by a muscular activation pattern with high EMG amplitude (475.7 µV) and low frequency (116.7 Hz) at 25 % MVC. The findings suggest that the CNS utilizes different muscular activation patterns to modulate RFD in ramp and ballistic contractions. In ramp contractions the EMG amplitude increased linearly with force. In ballistic contractions a high RFD is generated with a muscular activation pattern consisting of high amplitude and low frequency at the start of the contraction.